Synthesis and Structural Characterization of an Unusual Heterometallic Europium(III) Amidinate Complex12. Issue 12 (1st June 2015) - Sroor, Farid M.; Hrib, Cristian G.; Hilfert, Liane; Edelmann, Frank T.
Abstract: The reaction of EuI2 (THF)2 with 3 equiv. of the recently discovered lithium‐cyclopropylethinylamidinate Li[ c ‐C3 H5 –C≡C–C(NCy)2 ] (1 ) (Cy = cyclohexyl) unexpectedly afforded the heterometallic europium(III) amidinate complex [ c ‐C3 H5 –C≡C–C(NCy)2 Li c ‐C3 H5 –C≡C–C(NCy)2 2 Eu(μ‐I)2 Li(THF)2 ] (2 ) in the form of bright yellow, air‐ and moisture‐sensitive crystals. An X‐ray diffraction study of2 revealed several unusual structural features. It comprises a double "ate" complex of the tentative trivalent europium(III) bis(cyclopropylethinylamidinate) derivative [ c ‐C3 H5 –C≡C–C(NCy)2 ]2 Eu III I. "Ate" complex formation occurred not only through retention of one equiv. of lithium iodide but also through addition of one equiv. of Li[ c ‐C3 H5 –C≡C–C(NCy)2 ]. The Li atom in the iodo‐bridged Eu(μ‐I)2 Li(THF)2 part of the molecule is tetrahedrally coordinated, whereas the second lithium atom is only tricoordinate through the presence of a rare monodentate (dangling) amidinate ligand. Abstract :